Effective strategic leadership: Balancing roles during church transitions - Pearse, Noel J. (HTS teologiese studies, 2011)
As part of their responsibilities of leading the organisation, strategic leaders are responsible for leading change. This article investigated the application of the strategic leadership of change within the church context. A Straussian approach to the grounded theory method was used to generate a substantive grounded theory of organisational change and leadership, particularly focusing on the manifestation and management of organisation inertia in churches within South Africa that were transitioning from a programme based to a cell based church design. This article reported on one aspect of this study and focused on the patterns of leadership roles. It further distinguished between effective and ineffective leadership patterns that either enhanced or compromised the credibility of the leader and by implication, affected the success of the change intervention. The results of the study were discussed from the perspective of social capital theory, thereby contributing to understanding the role of strategic leaders in building social capital within the context of organisation change.